The Circulation of the Saints: A Study of People Who Join Conservative Churches - Bibby, Reginald W. (Journal for the scientific study of religion, 1973)
The authors suggest that confusion about differential growth rates among various kinds of churches might be clarified by examining the sources from which churches draw their new members. In the authors' investigation of membership additions to 20 evangelical congregations over a five-year period they found that over 70 percent of the new members came from other evangelical churches (reaffiliates such as migrants or transfers) while nearly another 20 percent were the children of members. Less than 10 percent were proselytes or converts from outside the evangelical community, and even these were primarily recruited from other churches or became members through intermarriage. This finding suggests interesting implications for evangelicals with the specific goal of proselytism. The authors argue that conservative churches may be growing faster than other churches because of their superior ability to retain their children and their mobile members.